A dinâmica territorial da cultura e do turismo em Mossoró/RN : uma análise geográfica - Amaral, Patrícia Daliany Araújo do (2008)
The city of Mossoró has been, currently, divulged and known in all Rio Grande do Norte as the cultural capital of the State, in function of the excellent carried through investments, each year, in the cultural sector. The present work is considered to construct an understanding to of the dynamics of the culture and tourism in the city of Mossoró. This work searches also , to verify how this territorial dynamics of the city is processed, by the recent years, in function of the local activities as Mossoró Cidade Junina , Auto da liberdade e Festa de Santa Luzia. An analysis of the occured territorial transformations in Mossoró has been done, decurrent of the activities in study, and the impacts proceeding from the public and private investments, that provoke a new dynamics in the city. Moreover, the perception of the community, the private initiative and the public power in relation to these practical is verified as processes of Mossoró. For this, documentary and bibliographical research has been used. It was accomplished, field research, through the comment not-participant and from the accomplishment of interviews with the municipal public power, main idealizer of the parties and with the private initiative, as sponsor. The local community also participated through the application of questionnaires. It has been concluded that the parties as Mossoró Cidade Junina, Auto da Liberdade and Santa Luzia, have demonstrated a capacity to create and to keep a tourism flow, being Mossoró projection as a tourist destination. The city has through it parties, great part of itself moving in direction to guarantee its accomplishment, what it makes with that its territorial dynamics comes being modified for and for the tourism